Electrophile induced branching cascade: a powerful approach to access various molecular scaffolds and their exploration as novel anti-mycobacterial agents - Patil, Nitin T.; Konala, Ashok; Sravanti, Sudha; Singh, Ashita; Ummanni, Ramesh; Sridhar, Balasubramanian (Chemical Communications, 2013)
Herein we report on the Electrophile Induced Branching Cascade (EIBC), a new technique to produce a variety of biologically important molecular scaffolds. Some compounds exhibit excellent activities against Mycobacterium smegmatis.

Relay catalytic branching cascade: technique to access diverse molecular scaffolds - Patil, Nitin T.; Shinde, Valmik S.; Sridhar, Balasubramanian (Angewandte Chemie International Edition, 2013)

Catalyst-free regioselective [3+2] cycloadditions of alpha,beta-unsaturated N-arylnitrones with alkenes to access functionalized isoxazolidines: a DFT study - Ghosh, Arnab; Mane, Manoj V.; Rode, Haridas B.; Patil, Siddappa A.; Sridhar, Balasubramanian; Dateer, Ramesh B. (Chemistry-An Asian Journal, 2020)
The catalyst-free regioselective [3+2]-cycloaddition of alpha,beta-unsaturated N-arylnitrones with alkenes are developed. The series of synthetically important functionalized isoxazolidines are prepared in good to excellent yields by step economic pathway under ligand and transition-metal-free conditions. The regioselective cycloaddition pathway supported by control experiment and computational study.
Keywords: DFT study; isoxazolidines; metal and ligand free; nitrone cycloaddition; Regioselective

Total synthesis and revision of stereochemistry of a natural benzo[g]isochromene stereodiad isolated from rubia philippinensis - Choudhury, Rahul; Miriyala, Satya Ravi Teja; Resmi, K. R.; Sridhar, Balasubramanian; Kasa, S. R. Krishna Murthy; Reddy, D. Srinivasa (Organic Letters, 2024)
This study presents a total synthesis and revision of the stereochemical configuration of the conformationally flexible natural product benzo[g]isochromene stereodiad alongside its diastereomeric counterparts. The highlights of the synthesis are the TiCl4-mediated diastereoselective aldol reaction, Pd-catalyzed lactonization, and Schmidt glycosidation. Our efforts using total synthesis disclosed herein proved that a previously assigned structure required revision.